Livre-arbítrio e a relação mente e cérebro em benjamim libet - Coelho, Jonas Gonçalves [UNESP] (My University, 2014)
My purpose is to reflect critically on how Benjamin Libet interprets his experiments, which are focused primarily on the question of free will. These experiments have often been considered as scientific evidence against free will, to the extent that they would have shown that the intention and will result from conscious brain processes, which are unconscious and precedents. But that is not the position of Libet, which distinguishes intention and conscious will, arguing that only the first results from previous and unconscious brain processes, while the second is autonomous and able to act causally on brain. Thus, Libet choose to ignore the suggestion of its initial experiments, that is, that all mental events result of specific brain processes. I argue that Libet ignores it because he is not able to understand how mental events, being essentially separated and at the same time the result of brain activity, could act causally on the brain.
Free will and the mind and brain relationship according to Benjamin Libet